Pushing Limits. - AYERS, ANDREW (Architectural Record, 2023)
The architects considered using structural cross-laminated timber (CLT) panels, "but, to ensure full future adaptability, we opted for a mass-timber frame, with wooden floors and facades too", explains Moreau. Construction of their Bruneseau building began just days before the French fire service issued a circular, on January 1, 2020, prohibiting exposed external wood until further notice. BUILDING TYPE STUDY 1,057 MULTIFAMILY HOUSING PLANNED IN the 1980s and officially launched in 1991, Paris Rive Gauche is the French capital's biggest redevelopment program since Haussmann's transformation of the city in the mid-19th century.